THE ROLE OF PSYCHOLOGY IN FORMING TEACHERS' PEDAGOGICAL ABILITY (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article describes the concepts of the role of psychology in the formation of pedagogical skills of teachers.